Modifikasi Pembelajaran Tolak Peluru Menggunakan Bola Tenis Di SMK Muhammadiyah 4 Kalisat - Danuarta, Rafli Jaya (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2025)
The purpose of this service is to make it easier for students at SMK Muhammadiyah 4 Kalisat to practice bullet shot skills properly and correctly through the modification of using a tennis ball as a tool. This service was carried out at SMK Muhammadiyah 4 Kalisat with the subject of 11th grade students of all majors while taking physical education, sports and health subjects. The problems experienced include the lack of adequate sports facilities, and the lack of teacher creativity. The implementation method is divided into three stages including preparation, implementation, and assessment and evaluation. The results of this service can improve students' skills in practicing bullet throwing and through a fun approach and the use of safer tools, students can understand the basic techniques of bullet throwing better.